Effects of Physical Training on Heart Rate Variability in Patients with Metabolic Syndrome: A Systematic Review and Meta-Analysis (2025)
Background/Objectives: Heart rate variability (HRV) is a reliable, non-invasive marker of autonomic nervous system function and is often impaired in individuals with metabolic syndrome (MetS). Physical exercise has emerged as an effective strategy to improve autonomic modulation; however, the comparative effects of different training modalities on HRV in individuals with MetS remain unclear. This systematic review and meta-analysis aimed to evaluate the impact of various exercise interventions on HRV and to identify which training types yield the most significant improvements. Methods: A systematic search was conducted in PubMed and Scopus up to April 2025. Eligible studies (n = 16) included adults with obesity and MetS (n = 752) who underwent structured exercise interventions with HRV assessments pre- and post-intervention. Standardized mean differences were calculated using random effects models. Subgroup analyses were performed based on training modality (endurance training [ET], resistance training [RT], high-intensity interval training [HIIT], and concurrent training [CT]). Results: Sixteen studies of moderate to high quality were included, with eleven studies eligible for meta-analysis. ET and HIIT significantly improved time-domain indices (Root mean square of differences of successive R-R intervals —rMSSD—, Standard deviation of the R-R interval series —SDNN—) and frequency-domain parameters (high-frequency —HF—), suggesting enhanced parasympathetic activity. RT showed inconsistent effects, while CT improved long-term HF and total power (TP). Non-linear indices were the least reported due to insufficient data. Conclusions: Physical exercise—particularly ET and HIIT—appears to enhance cardiac autonomic modulation in individuals with obesity and MetS. These findings support incorporating targeted training strategies into clinical practice to optimize cardiovascular health in these populations.